Space vector modulation‐included commutation method for voltage source‐type isolated three‐phase/single‐phase matrix converter. Issue 4 (3rd January 2018) - Haruna, Junnosuke; Funato, Hirohito; Ueda, Hiroshi
Abstract : This paper proposes a control strategy for voltage source‐type isolated AC/DC matrix converter. In this paper, differences of control strategy between a current source‐type and a voltage source‐type isolated AC/DC matrix converter are discussed by using instantaneous space vector diagrams. In addition, a commutation scheme of the voltage source‐type isolated matrix converter is proposed. The operation of proposed space vector modulation and commutation method is confirmed by the simulation results. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.